Sensuous proximity in research methods with expert teams, media sports, and esports practices - Witkowski, Emma (MedieKultur: Journal of media and communication research, 2018)
This paper examines epistemological issues in game studies research, specifically exploring qualitative research approaches to networked, expert computer game teams who engage in esports practices. Expert teams deliver their expert practice in part through interembodied sensitivities to sensorial team-based phenomena, which is made across multiple bodies and machines in the process of play. Drawing on fieldwork with World of Warcraft Arena tournament esports teams and research methods orientations from games studies, sensuous ethnography, and sports studies, a position of sensuous proximity in games research is explored and developed as a suite of research guidelines for engaging with esports teams high performance practices. I suggest a research approach that involves differing lenses and stances in the study of embodied team play, and varying scales of sensuous proximity to the layers of expert team practices that augmens the notion of playing research in game studies.